2017
DOI: 10.1038/srep45057
|View full text |Cite
|
Sign up to set email alerts
|

Significant Role of Collagen XVII And Integrin β4 in Migration and Invasion of The Less Aggressive Squamous Cell Carcinoma Cells

Abstract: Collagen XVII and integrin α6β4 have well-established roles as epithelial adhesion molecules. Their binding partner laminin 332 as well as integrin α6β4 are largely recognized to promote invasion and metastasis in various cancers, and collagen XVII is essential for the survival of colon and lung cancer stem cells. We have studied the expression of laminin γ2, collagen XVII and integrin β4 in tissue microarray samples of squamous cell carcinoma (SCC) and its precursors, actinic keratosis and Bowen’s disease. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 42 publications
0
29
0
Order By: Relevance
“…Immunohistochemical analysis exhibited stronger immunoreaction of collagen XVII ectodomain in the primary SCC tumor and associated metastases (51). This is similarly noted in atypical keratinocytes of actinic keratoses and SCC in situ (51,52). Viral mediated RNA interference knockdown of collagen XVII and/or β4 disrupted the migration and invasion of less aggressive SCC cells (52).…”
Section: Squamous Cell Carcinomamentioning
confidence: 80%
See 2 more Smart Citations
“…Immunohistochemical analysis exhibited stronger immunoreaction of collagen XVII ectodomain in the primary SCC tumor and associated metastases (51). This is similarly noted in atypical keratinocytes of actinic keratoses and SCC in situ (51,52). Viral mediated RNA interference knockdown of collagen XVII and/or β4 disrupted the migration and invasion of less aggressive SCC cells (52).…”
Section: Squamous Cell Carcinomamentioning
confidence: 80%
“…Viral mediated RNA interference knockdown of collagen XVII and/or β4 disrupted the migration and invasion of less aggressive SCC cells (52). Of note, no impact was observed on HSC-3, a highly invasive cell with upregulated collagen XVII (52).…”
Section: Squamous Cell Carcinomamentioning
confidence: 97%
See 1 more Smart Citation
“…Functional enrichment analysis has been used to reveal biological functions of mRNAs, ceRNA counterparts of lncRNA (39). As a result, three differentially enrichment GO terms(collagen binding (40), extracellular matrix binding (29) and cell adhesion molecule binding(31))…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it has been reported that AhR expression silencing or knockdown results in higher migration and invasion (Lee et al, ; Rico‐Leo, Alvarez‐Barrientos, & Fernandez‐Salguero, ). Furthermore, downregulation of β4 integrin inhibited cell invasion and migration in different cancer cells (Moilanen et al, ; Zhang et al, ). Therefore, one can conclude that lower AhR expression and elevated β4 integrin level can play a role in the invasion/migration process.…”
Section: Discussionmentioning
confidence: 99%